2015
DOI: 10.1371/journal.pone.0123852
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Zymography Differentiates Gelatinase Isoforms in Stimulated Microglial Cells and in Brain Tissues of Acute Brain Injuries

Abstract: Excessive activation of gelatinases (MMP-2/-9) is a key cause of detrimental outcomes in neurodegenerative diseases. A single-dimension zymography has been widely used to determine gelatinase expression and activity, but this method is inadequate in resolving complex enzyme isoforms, because gelatinase expression and activity could be modified at transcriptional and posttranslational levels. In this study, we investigated gelatinase isoforms under in vitro and in vivo conditions using two-dimensional (2D) gela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
(69 reference statements)
1
7
0
1
Order By: Relevance
“…The gelatinolytic activities of MC3T3-E1 cell supernatants were determined via gelatin zymography assay (Xinfan Technology, Shanghai, China) according to the manufacturer’s instructions. HT1080 (human fibrosarcoma) cell media conditioned for 24 h was used as a positive control, as it is enriched with gelatinases [ 47 ]. Supernatants were collected from culcured cells and examined with 8% polyactylamide gels containing 0.1% gelatin.…”
Section: Methodsmentioning
confidence: 99%
“…The gelatinolytic activities of MC3T3-E1 cell supernatants were determined via gelatin zymography assay (Xinfan Technology, Shanghai, China) according to the manufacturer’s instructions. HT1080 (human fibrosarcoma) cell media conditioned for 24 h was used as a positive control, as it is enriched with gelatinases [ 47 ]. Supernatants were collected from culcured cells and examined with 8% polyactylamide gels containing 0.1% gelatin.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Chen et al, by using 2D gelatin zymography were able to detect organomercuric chemical 4-aminophenylmercuricacetate-induced activation of MMP-2 isoforms with variant pI values in the conditioned medium of human fibrosarcoma cells and also several MMP-9 pro-forms, with different pI values, in murine LPS-stimulated BV-2 cells [40].…”
Section: +mentioning
confidence: 99%
“…Nevertheless, we observed that MMP-9 was the predominant gelatinase under our experimental conditions. 8,20,21,32 It should be noted, however, that our present ACPPs do not discriminate between MMP-2 and MMP-9, although we are actively developing more selective ACPPs.…”
Section: Discussionmentioning
confidence: 77%